Mummy Stories - Piombino-Mascali, Dario (Archaeologia Lituana, 2019)
This article represents a summary of the author’s past 12 years of research on several mummy sets. As mummy studies expand as a sub-specialty of biological anthropology, it is important to highlight the significant contribution that the study of preserved remains can provide to both archaeology and history.
Keywords: death; mummification; bioarchaeology; paleopathology; taphonomy